2011
DOI: 10.1136/amiajnl-2010-000053
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a survey instrument for assessing prescribers' perception of computerized drug-drug interaction alerts

Abstract: We developed and empirically validated a survey instrument that may be useful for future research on DDI alerts and other types of computerized medication safety alerts more generally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 90 publications
0
22
0
Order By: Relevance
“…We started from the hypothesis that satisfaction with a specific technological tool could be one dimensional, although some authors recommend considering more domains 26. Different tools have been used to measure satisfaction with CPOE,15 most of which were developed by the researchers themselves 24.…”
Section: Discussionmentioning
confidence: 99%
“…We started from the hypothesis that satisfaction with a specific technological tool could be one dimensional, although some authors recommend considering more domains 26. Different tools have been used to measure satisfaction with CPOE,15 most of which were developed by the researchers themselves 24.…”
Section: Discussionmentioning
confidence: 99%
“…Although the TAM model has been applied across a number of health contexts and technologies [26,27] only few studies related to medication safety [15,59], CDSS [46,58] or the ED context [60] could be identified. To our knowledge, TAM2 has not been previously applied in the ED area making this one of the first studies of its kind.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that computerized CDSS were not successful due to limited or no system use [10-14]. The launch of such systems requires an adequate awareness and the determination to alter existing medication procedures, thus making user acceptance a key factor for successful implementation [15]. Several methods and models have been published to examine factors which influence the acceptance of innovations.…”
Section: Introductionmentioning
confidence: 99%
“…17 Although systematically evaluating DDI alert satisfaction is recommended, only 1 known survey instrument has been developed and evaluated psychometrically. 18 The developers of this tool recommended that it be used as part of comprehensive efforts to assess clinicians, including alert data and metrics. 18 However, we did not find published studies in which this tool was used to guide DDI alert improvement efforts.…”
mentioning
confidence: 99%
“…18 The developers of this tool recommended that it be used as part of comprehensive efforts to assess clinicians, including alert data and metrics. 18 However, we did not find published studies in which this tool was used to guide DDI alert improvement efforts.…”
mentioning
confidence: 99%